Large-scale facilitative effects for a single nurse shrub: Impact of the rainfall gradient, plant community and distribution across a geographical barrier - Velasco, Nicolás (2024)
Fil: Velasco, Nicolás. University of Groningen. Institute for Evolutionary Life Sciences. Conservation Ecology Group; The Netherlands.